Mediastinoscopy: safety and utility Cervical mediastinoscopy: assessing mediastinal lymphadenopathy at Manmohan Cardio-thoracic Vascular and Transplant center (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Mediastinoscopy is considered essential in staging of lung cancer and evaluation of mediastinal lymphadenopathy and masses. This facility has only recently been available at our center. We review our initial experience and analyse its safety and utility in our setting.Methods: Retrospective analysis of data of all patients who underwent cervical mediastinoscopy at Manmohan Cardio-thoracic Vascular and Transplant Center (MCVTC) was done. Demographic, clinical and perioperative data were recorded. Concordance of pre and post-operative diagnosis was studied.Results: Between January 2012 and April 2014, 24 patients underwent mediastinoscopy. The age ranged from 28-75 years (mean = 43.12 ± 15.14). Females outnumbered males (M: F = 3:5). Mediastinoscopy was done for staging of lung cancer in six patients and for assessment of mediastinal lymphadenopathy in 18 patients. One patient had a minor preoperative bleeding. One patient developed surgical site infection. The post-operative stay ranged from 1-4 days (mean = 2.15 ± 0.75). Concordance of pre and postoperative diagnosis was seen in 14 (58%) patients. Amongst the five patients pre-operatively thought to have tubercular mediastinal lymphadenopathy; Tuberculosis was confirmed in only three. Only one of six patients in whom mediastinoscopy was done as a staging procedure in lung cancer was found to have malignant spread in the sampled nodes.Conclusion: Mediastinoscopy is safe and efficacious in diagnosing mediastinal lymphadenopathy. It should be routinely considered in staging of NSCLC and evaluation of enlarged mediastinal nodes.